The Philosophy of Law: A Bhartiya and Comparative Jurisprudential Inquiry - Makhija, Rashi; Jha, Anuradha (Trinity Law Review, 2025)
Jurisprudence constitutes the pivotal part of legal studies. It enlightens us on what law is, why it exists, its evolution, and its practical implications. This research article is entirely devoted to Bhartiya and Comparative Jurisprudential Inquiry. It demonstrates how both Indian (Bhartiya) and Western legal systems ‘developed their own legal thoughts. It is in ancient India that the idea of Dharma developed, which is the idea of Dharma. Dharma meant doing what is right, both legally and ethically. Dharma was law as observed in the Vedas and Manusmriti. Western thinkers like Austin and Hart were more inclined on a rational definition of law as commands and rules. This article examines issues such as the origins of law (customs, morality, legislation and judicial decisions), the legal system of India, the practice of law in ancient villages, and contemporary court operations. It also discusses schools of thought like natural law, legal positivism, and the historical and sociological perspectives of law. Most importantly, it demonstrates that law is not merely the domain of courts and punishment; it is also about justice, fairness, and resolver of societal issues. It helps students appreciate the interplay between ancient ideas and contemporary systems which shape the law we observe today.